KAIDAH FIQH DALAM FATWA EKONOMI DSN-MUI - Tika Mutiani; Muhamad Burhanuddin (Jurnal Ilmiah Ekonomi Islam, 2023)
The rules of fiqh are one of the important things as a guide for Muslims to solve legal problems they face in everyday life. Without guidelines, they cannot know the boundaries of whether something is permissible to do, nor can they determine which actions are more important to do or which are more important to abandon. Likewise, along with the development of sharia economic cases, it certainly requires regulations related to operational suitability according to sharia principles. Based on this, the idea of forming the DSN emerged. In the Indonesian context, the ideas for producing fatwas on sharia economic products and services actually come from the ijtihad of scholars who are members of an official intuition called the National Sharia Council-Indonesian Ulema Council or DSN-MUI. Therefore, according to its identity the DSN-MUI has a strategic role in the dynamics of the religious life of the community, including economic issues.